Special Issue on “Advances in Organic Corrosion Inhibitors and Protective Coatings” - Ioannis A. Kartsonakis (Applied Sciences, 2020)
This Special Issue collects new findings and recent advances in the development, synthesis, and structure–activity relationships of organic corrosion inhibitors and protective coatings.